A cross-sectional study of prevalence and types of sexual dysfunction among married male patients with alcohol dependence syndrome attending tertiary healthcare center from Central Rural India - Ravi Singh Bhainsora; Pradeep Shriram Patil; Ajinkya Sureshrao Ghogare; Ganpatlal Kodarbhai Vankar (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Chronic and persistent alcohol use is one of the most common significant psychiatric illnesses known to cause sexual dysfunction. The aim of the present study is to study the prevalence and types of sexual dysfunction in the clinical sample of married male patients with alcohol dependence syndrome (ADS). MATERIALS AND METHODS: The present cross-sectional study was conducted in a tertiary healthcare center from Central Rural India over an 18-month period (from November 1, 2017, to April 30, 2019), with a sample size of 100 patients with diagnosis of ADS. Data were collected using convenient sampling method from married male patients diagnosed with ADS, based on the International Classification of Mental and Behavioral Disorders, 10th Edition-Diagnostic Criteria for Research. Sociodemographic profile and clinical variables were recorded in a specific case report form prepared for the study using the severity of alcohol dependence questionnaire (SADQ) to assess the severity of ADS and using Arizona sexual experiences scale (ASEX) to assess the types and prevalence of sexual dysfunction among patients with ADS. Data were collected and analyzed using SPSS Software Version 15.0, Chi-square test, and Pearson's test of correlation. RESULTS: Of the 100 patients of ADS assessed, 48% had sexual dysfunction. Majority of the patients reported more than one sexual dysfunction with 87.5% of the patients reporting reduced sexual drive, 79.1% of the patients reported dysfunction in sexual arousal, while erectile dysfunction was found in 58% of the patients. 54% of the patients reported difficulty in reaching orgasm. The lowest prevalence in our study was of orgasmic satisfaction reported by 31.2% of the patients. There was high positive correlation between SADQ scores and ASEX scores. Thus, as the severity of ADS increased, the risk of development of sexual dysfunctions also increased. Further, there was comparatively low but positive correlation between duration of ADS and sexual dysfunction on ASEX scores, indicating that as the duration of ADS increased, the risk of occurrence of sexual dysfunctions also increased. CONCLUSION: Chronic and severe alcohol dependence increases the chances of developing sexual dysfunctions. These findings can be utilized in the motivation enhancement therapy of patients with ADS to quit alcohol consumption and to improve their quality of sexual life.